CLIL IN TOURISM STUDENTS' MULTICULTURAL COMPETENCE DEVELOPMENT - Inna Goncharova; Olena Lazebna; Viktoriia Kotvytska (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The current study aims at implementation of the Content and Language Integrated Learning (CLIL) as an educational approach in tourism students' multicultural competence development. To achieve the goal, a mixed-method was chosen, which implied the use of quantitative and qualitative research methods. The quantitative method was used to process the test results of tourism students and determine the statistical significance of the results obtained during the experiment, the qualitative method was used to analyse and interpret the results. 25tourism students of V. I. Vernadsky Taurida National University took part in the experimental study in 2020-2021 academic year. According to the results, due to CLIL classes the students' theoretical knowledge and practical skills in the field of tourism, the ability to interact with representatives of other countries and cultures and to solve professional problems in the conditions of foreign language communication in the intercultural environment, have been increased. Additionally, the knowledge, skills and abilities of the tourism students; the pedagogical conditions of successful CLIL implementation; the methodological recommendations for developing the multicultural competence on the base of CLIL and the specifics of implementing CLIL in the educational process of the tourism students were defined. It was concluded that the use of CLIL in tourism students' multicultural competence development helps to diversify foreign language learning at the university level and facilitates the development of professional communicative skills.